Hyponatremia in Acute Heart Failure in Relation to Hematocrit Levels: Clinical Relevance and Prognostic Implication - Ruocco, Gaetano (Cardiorenal Med, 2018)
BACKGROUND: Hyponatremia is the most common electrolyte abnormality found in hospitalized patients with acute heart failure (AHF) and is related to poor prognosis. This study sought to evaluate: (1) the different prognostic impact of dilutional versus depletional hyponatremia, evaluating short- and long-term outcome; (2) the relationship between both types of hyponatremia and intravenous furosemide dose, renal function changes, and persistent congestion at discharge. METHODS: This retrospective single-center study included 233 consecutive patients with a primary diagnosis of AHF. Hyponatremia was defined as serum sodium < 135 mEq/L, which could be either dilutional (hematocrit < 35%) or depletional (hematocrit ≥35%). Persistent congestion was defined as a congestion score ≥2 at discharge. Patients were followed 180 days for occurrence of death or rehospitalization for AHF. RESULTS: Hyponatremia was present in 68/233 patients with 27 cases classified as dilutional hyponatremia versus 41 as depletional. The proportion of patients with persistent congestion was higher in the dilutional hyponatremia group, but similar in the depletional hyponatremia group (52 vs. 81 vs. 58%; p = 0.02). After adjustment for important baseline characteristics, dilutional hyponatremia was significantly associated with the risk of death or rehospitalization for AHF at 60 days (HR 2.17 [1.08–4.37]; p = 0.03) and 180 days (HR 1.88 [1.10–3.21]; p = 0.02). In contrast, depletional hyponatremia was only significantly associated with the same endpoint at 180 days (HR 1.64 [1.05–2.57]; p = 0.03). CONCLUSIONS: Low hematocrit levels in AHF patients with hyponatremia characterize a population that is more difficult to decongest and has poor clinical outcome. In contrast, patients with hyponatremia but normal hematocrit are better decongested and have better short-term outcome.